The effect of diesel-biodiesel blends on the performance and exhaust emissions of a direct injection off-road diesel engine - Mickevičius, Tomas; Slavinskas, Stasys; Wierzbicki, Slawomir; Duda, Kamil (Transport, 2014)
This paper presents a comparative analysis of the diesel engine performance and emission characteristics, when operating on diesel fuel and various diesel-biodiesel (B10, B20, B40, B60) blends, at various loads and engine speeds. The experimental tests were performed on a four-stroke, four-cylinder, direct injection, naturally aspirated, 60 kW diesel engine D-243. The in-cylinder pressure data was analysed to determine the ignition delay, the Heat Release Rate (HRR), maximum in-cylinder pressure and maximum pressure gradients. The influence of diesel-biodiesel blends on the Brake Specific Fuel Consumption (bsfc) and exhaust emissions was also investigated. The bench test results showed that when the engine running on blends B60 at full engine load and rated speed, the autoignition delay was 13.5% longer, in comparison with mineral diesel. Maximum cylinder pressure decreased about 1–2% when the amount of Rapeseed Methyl Ester (RME) expanded in the diesel fuel when operating at full load and 1400 min–1 speed. At rated mode, the minimum bsfc increased, when operating on biofuel blends compared to mineral diesel. The maximum brake thermal efficiency sustained at the levels from 0.3% to 6.5% lower in comparison with mineral diesel operating at full (100%) load. When the engine was running at maximum torque mode using diesel – RME fuel blends B10, B20, B40 and B60 the total emissions of nitrogen oxides decreased. At full and moderate load, the emission of carbon monoxide significantly raised as the amount of RME in fuel increased.First Published Online: 16 Dec 2014